Resistance gene expression in selected Indonesian pigmented rice varieties against infection by Xanthomonas oryzae pv. oryzae - Nur Elia Nadhira; Ali Wafa; Wahyu Indra Duwi Fanata; Hardian Susilo Addy (Universitas Gadjah Mada, 2022)
Rice (Oryza sativa L.) production is limited by bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae (Xoo). For decades, researchers have attempted to control this disease by growing plants with blight‐resistant Xa genes. Genetic resources often vary between rice varieties, and there is little information about the genetic resources of the pigmented rice varieties widely grown in Indonesia and their resistance genes against Xoo. The purpose of this study was to determine the expression of Xa genes in pigmented rice such as Inpari 24 and Cempo Merah (red‐pigmented) along with Hitam Bantul (black‐pigmented) and white rice varieties IR64 and Ciherang, and to evaluate their resistance to BLB. All varieties carried the Xa4, Xa10 and xa13 genes but varied in the Xa1, Xa7 and Xa21 genes. The rice varieties expressed some of these genes only after inoculation with Xoo. Disease assessment categorised the three different pigmented rice varieties as resistant (Ciherang, Cempo Merah and Hitam Bantul), while IR64 (white) and Inpari 24 (red) were moderately resistant. There was no specific pattern of Xa genes possession, quality of expression or resistance level to X. oryzae pv. oryzae. Therefore, when breeding plants, the selection of parental variety must be considered in terms of the possession and expression of Xa genes such as Xa10 as a molecular marker for resistance.